Penerapan Pembelajaran PKn untuk Meningkatkan Motivasi Belajar pada Materi Bhinneka Tunggal Ika di Sekolah Dasar - Khairani, Intan; Nasution, Khairunnisa; Lubis, Zaira Asmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out the application of civic education in improving students' learning motivation on the material of Unity in Diversity in Elementary School. This type of research is descriptive with a qualitative approach. Qualitative research methods are used to deeply examine the research object without trying to manipulate the research, but rather studying a phenomenon. The results of the research on fifth grade students show that there are still some students who are less motivated in learning civic education, especially in the material of Unity in Diversity, because they have difficulty understanding the teacher's explanation. Learning about Unity in Diversity is expected to create an attitude of mutual respect among students so that they can apply it in daily life and increase student motivation through the use of more active and enthusiastic learning media. Teachers also face difficulties due to the lack of creative and innovative learning media, where they only rely on material from textbooks, making it difficult for students to understand Unity in Diversity in daily life.